Aspiration, Consumer Culture, and Individualism in Les Belles-Sœurs - Julie Robert (Studies in 20th & 21st Century Literature, 2014)
The premise of Michel Tremblay’s revolutionary 1968 play, Les Belles-Sœurs, is a working bee. A group of working-class women gather to paste a million trading stamps, won in a sweepstakes, into booklets that once full can be redeemed for household goods. As the guests surreptitiously pilfer what they see as their hostess’s underserved windfall, their actions problematize the links between the individualistic aspects of consumer and material culture and the communal values they share as members of Quebec’s working class. Taking consumer culture and material desire as a starting point, this essay considers the relationship between the individual and the collective inherent in such matters and situates it in relation to the ways in which consumer culture, individual advancement, and national projects of collective betterment, namely the Quiet Revolution, are implicitly treated in the play. It is argued that Tremblay does not resolutely condemn consumer culture as something apart from the monumental social and political changes of the era, but rather sees in the practices of consumerism aspects of collective behavior that trouble interpretations of the accumulation of material goods as selfish or individualistic undertakings.
Keywords: Consumer culture; Individualism; Les Belles-Sœurs; Aspirational identity